Allele-specific depletion of GNAQQ209L via siRNA or an rAAV2-shRNA vector induces selective toxicity in GNAQQ209L uveal melanoma cells - Trace F. McCall; Emma J. Sawyer; Joshua Darnell; Matthew L. Hirsch; Jacquelyn J. Bower (Molecular Therapy: Oncology)
Approximately 80%–90% of uveal melanomas (UVM) harbor a single base pair substitution in one of two Gα protein subunits (GNAQQ209L/P/GNA11Q209L), resulting in constitutive activation and tumor initiation/progression. Herein, a small interfering RNA (siRNA) that specifically targets GNAQQ209L transcripts induced significant cell death in GNAQQ209L UVM cells, whereas little to no effects were observed on GNAQwt cells or GNAQwt transcripts. The most effective siRNA sequence was subsequently encoded into a short hairpin RNA (shRNA) cassette (shGNAQQ209L), expressed in a recombinant adeno-associated virus (rAAV), and the AAV2 capsid was selected for viral production upon completion of a serotype survey in UVM cells. Transduction with rAAV2-shGNAQQ209L induced significant cell death in GNAQQ209L cells but not in a GNAQwt UVM line. Unexpectedly, cell death in the GNAQQ209L UVM cells was also observed upon transduction with the non-targeting control rAAV2 (although to a lesser degree than rAAV2-shGNAQQ209L), suggesting that an element of the AAV vector itself exhibits toxicity in GNAQQ209L UVM cells. This work is among the first describing a genetic-based rAAV approach to specifically target an oncogenic mutant driver allele using single base pair allelic discrimination, collectively demonstrating that both siRNA and rAAV methods of GNAQQ209L depletion result in significant UVM cell death.